PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PEGADAIAN KOTA SUNGAI PENUH - Elex Sarmigi; Lia Angela; Tiara Tiara (Jurnal Ekonomi Dan Bisnis, 2022)
This study aims to examine the effect of training and work discipline on employee performance. The population of this research are pawnshop employees in Sungai Penuh City. To collect data, this study used a questionnaire. The data collected was then analyzed using statistical analysis tools, namely multiple regression analysis using the IBM SPSS 25 application. The results of this study indicate that both partially or simultaneously Training and Work Discipline have a positive and significant effect on Employee Performance at the Pegadaian Kota Sungai Penuh.